Scientific nursing production from the perspective of social representation: Brazil, 1975-2001 La producción científica de la enfermería en la perspectiva de la representación social: Brasil, 1975-2001 A produção científica da enfermagem na perspectiva da representação social: Brasil, 1975-2001 - Sergio Corrêa Marques; Maria Antonieta Rubio Tyrrell; Denize Cristina de Oliveira (Universidade de São Paulo, 2006)
This study aimed to: survey the number of nursing theses and dissertations produced between 1975 and 2001 with a social representation approach (RS); characterize the products with regard to the institution of origin, country region, study subjects and representation objects; to group in to theme categories and research lines in nursing. The data were collected from the Center of Studies and Research in Nursing at the Brazilian Nursing Association. The result evidenced 131 studies with RS support, originated in 1990, with higher production in the year 2000, mainly in the South East (83.1%). It registered 145 subjects; the most common objects are "disease", "health-disease process", "nurses' professional practice" and "care delivery". In the thematic categorization, the care area joins the greatest quantity of studies. In short, nursing has been seeking to appropriate itself of this theoretical-methodological framework as the basis and guide for part of its knowledge production. Este estudio objetivó: inventariar el número de tesis y disertaciones de enfermería del período de 1975 a 2001 con aproximación de las representaciones sociales (RS); caracterizar las producciones con relación a la institución de origen, a las regiones del país, a los sujetos de los estudios y objetos de representación; reunir en las categorías temáticas y lineas de investigación en enfermería. Los datos fueron recolectados del catálogo del Centro de Estudios y Pesquisas en Enfermería/ Asociación Brasileña de Enfermería. El resultado evidenció 131 estudios con soporte de las RS, producidos desde 1990, con mayor producción en el año de 2000, principalmente en la Región Sudeste (83,1%). Se registraron 145 sujetos; los objetos más comunes fueron "enfermedad", "proceso salud-enfermedad", "práctica profesional del enfermero" y el "cuidar". En la categorización temática, el área de atención es el que reúne el mayor número de investigaciones. En resumen, la Enfermería busca apropiarse de este referencial teórico y metodológico en el embasamiento y guía de parte de la producción de su conocimiento. O presente estudo objetivou: levantar os quantitativos de teses e dissertações de enfermagem do período entre 1975 e 2001, com abordagem das representações sociais (RS), caracterizar as produções em relação à instituição de origem, às regiões do país, aos sujeitos dos estudos e objetos de representação, agrupar nas categorias temáticas e linhas de pesquisa em enfermagem. Os dados foram coletados do catálogo do Centro de Estudos e Pesquisas em Enfermagem da Associação Brasileira de Enfermagem. O resultado evidenciou 131 estudos com suporte das RS, originados em 1990, com maior produção no ano de 2000, principalmente na Região Sudeste (83,1%). Registrou-se 145 sujeitos, os objetos mais comuns são "doença", "processo saúde-doença", "prática profissional do enfermeiro" e o "cuidar". Na categorização temática, a área assistencial é a que reúne a maior quantidade de pesquisas. Em suma, a enfermagem vem procurando se apropriar desse referencial teórico-metodológico na fundamentação e guia de parte da produção do seu conhecimento.